THE VAGINAL AND ENDOMETRIAL MICROBIOME IN ASSISTED REPRODUCTIVE TECHNOLOGY (ART) - Agnieszka Krajewska; Adrianna Kowalik; Agnieszka Korzeniewska; Julia Dębczak; Karolina Łuczak; Katarzyna Tłustochowicz; Magdalena Korba; Natalia Malicka; Wiktoria Polkowska (International Journal of Innovative Technologies in Social Science, 2026)
Background: Infertility affects a substantial proportion of the global population, and assisted reproductive technologies (ART) do not guarantee success. Increasing evidence suggests that the vaginal and endometrial microbiomes play a critical role in female reproductive health, influencing implantation, pregnancy maintenance, and ART outcomes. Objective: This narrative review aims to synthesize current evidence on the composition of the vaginal and endometrial microbiota and to explore biological mechanisms linking microbial profiles with reproductive success in ART. Materials and Methods: A comprehensive narrative review of published literature was conducted, focusing on studies evaluating vaginal and endometrial microbiota composition, associated immunological and metabolic mechanisms, and reproductive outcomes in natural conception and ART cycles. Results: In healthy reproductive-age women, a Lactobacillus-dominant vaginal and endometrial microbiome is associated with enhanced immune tolerance, epithelial barrier integrity, and metabolic activity supporting endometrial receptivity. Lactobacilli regulate local immune responses via anti-inflammatory cytokine signaling, modulation of pattern recognition receptor pathways, and production of metabolites involved in prostaglandin synthesis, angiogenesis, and uterine contractility. In contrast, dysbiotic communities enriched in non-Lactobacillus taxa are linked to increased pro-inflammatory signaling, impaired decidualization, mucosal barrier disruption, and altered immune cell balance. Clinical studies consistently report higher implantation, clinical pregnancy, and live birth rates in women with Lactobacillus-dominant microbiota; however, methodological heterogeneity limits causal interpretation. Emerging microbiome-modulating interventions, including probiotics, antibiotics, and vaginal microbiota transplantation, show potential but remain experimental. Conclusions: A Lactobacillus-dominant reproductive tract microbiome appears strongly associated with improved ART outcomes. Standardized prospective and interventional studies are needed to establish clinically relevant microbial biomarkers and develop effective microbiome-targeted therapies.